Pengaruh Kepemimpinan Transformasional dan Reward pada Kontribusi Berbagi Pengetahuan dengan Praktik Berbagi Pengetahuan sebagai Variabel Pemediasi di SMK Negeri 2 Depok Yogyakarta - Sekar Arum Kinasih; Handrio Adhi Pradana (Universitas Batanghari, 2022)
The purpose of this study was to examine and analyse the mediation effect of knowledge sharing practices in relationship among transformational leadership and reward on contribution to knowledge sharing. This research was quantitative and using questionnaire as data collection method. A total of 172 samples were taken using the census method. Data analysis methods was used in this research, including t-test, F-test, simple and multiple regression analysis, and path analysis with Sobel technique to examine the mediating effect. This study revealed that transformational leadership and reward has a significant and positive influence toward both of contribution to knowledge sharing and knowledge sharing practices. Contribution to knowledge sharing is also affected positively significant by knowledge sharing practices. Moreover, knowledge sharing practices mediate the relationship between transformational leadership and reward on contribution to knowledge sharing. This study confirms the role of knowledge sharing practices in encouraging leadership styles and rewards to generate optimal employee performance results. Theoretical and practical contributions are elaborated in the discussion section.